2022
DOI: 10.3390/mi13020335
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High Surface Area Microporous ZnO from ZnO/Carbon Sacrificial Composite Monolith Template

Abstract: Fabrication of porous materials from the standard sacrificial template method allows metal oxide nanostructures to be produced and have several applications in energy, filtration and constructing sensing devices. However, the low surface area of these nanostructures is a significant drawback for most applications. Here, we report the synthesis of ZnO/carbon composite monoliths in which carbon is used as a sacrificial template to produce zinc oxide (ZnO) porous nanostructures with a high specific surface area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Based on the ZnO sensor’s surface, when adsorbed molecular oxygen under UV activation captures photogenerated free electrons, they result in the chemisorption of oxygen ions to ZnO surface following: O 2 (g) + e − →O 2 − (ads) or O 2 (g) + e − →2O − (ads), leaving photo-induced holes in the low-conductivity depletion layer (or space charge region, SCR). According to the space charge model [ 25 , 54 ], there will be upward band-bending near the surface for both the conduction and valence bands shown in Figure 5 a. As a result, there is an increase in energy barrier height for electron transfer between the grains or across neighboring T–ZnO arms, i.e., the qV s1 , and thus the overall conductance is reduced (alternatively, increasing resistance).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the ZnO sensor’s surface, when adsorbed molecular oxygen under UV activation captures photogenerated free electrons, they result in the chemisorption of oxygen ions to ZnO surface following: O 2 (g) + e − →O 2 − (ads) or O 2 (g) + e − →2O − (ads), leaving photo-induced holes in the low-conductivity depletion layer (or space charge region, SCR). According to the space charge model [ 25 , 54 ], there will be upward band-bending near the surface for both the conduction and valence bands shown in Figure 5 a. As a result, there is an increase in energy barrier height for electron transfer between the grains or across neighboring T–ZnO arms, i.e., the qV s1 , and thus the overall conductance is reduced (alternatively, increasing resistance).…”
Section: Resultsmentioning
confidence: 99%
“…T–ZnO has also shown improved carrier mobility over zero-dimensional (0D) nanostructures, resulting in faster response and recovery times, comparable to those of one-dimensional (1D) nanostructures [ 8 , 24 ]. It also has a wide-ranging BET surface area, which can vary anywhere between 5 and 78 m 2 /g depending upon the morphological structure [ 25 , 26 ]. Thepnurat et al fabricated UV sensors utilizing interconnected T–ZnO that showed promising results due to the linked tetrapod arms, which decrease the potential barrier at grain boundaries, thereby improving UV-induced charge carrier mobility [ 20 ].…”
Section: Introductionmentioning
confidence: 99%